2019
DOI: 10.3390/ijns5020021
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Fast, Robust, Inexpensive, Two-Tiered Neonatal Screening Test algorithm on Dried Blood Spots for Spinal Muscular Atrophy

Abstract: Spinal muscular atrophy (SMA) is one of the leading genetic causes of infant mortality with an incidence of 1:10,000. The recently-introduced antisense oligonucleotide treatment improves the outcome of this disease, in particular when applied at an early stage of progression. The genetic cause of SMA is, in >95% of cases, a homozygous deletion of the survival motor neuron 1 (SMN1) gene, which makes the low-cost detection of SMA cases as part of newborn screening programs feasible. We developed and validated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…MLPA was the second-tier test used, performed on blood samples collected in EDTA tubes, as the already established routine in our center. The use of DBS on MLPA was investigated by Strunk et al [32] and could facilitate the workflow implementation. The authors reported 100% sensitivity and specificity of the MLPA test (P021, MRC-Holland) using crude lysates from DBS (NaOH protocol).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLPA was the second-tier test used, performed on blood samples collected in EDTA tubes, as the already established routine in our center. The use of DBS on MLPA was investigated by Strunk et al [32] and could facilitate the workflow implementation. The authors reported 100% sensitivity and specificity of the MLPA test (P021, MRC-Holland) using crude lysates from DBS (NaOH protocol).…”
Section: Discussionmentioning
confidence: 99%
“…Dried blood spots (DBS) were stored in low-permeability zip-lock bags with silica gel desiccant packs at 4 • C (up to six months) and at −20 • C if longer prior to DNA extraction. The DNA was obtained from DBS, as described in Strunk et al [32]. Briefly, a single 3.2-mm punch was incubated at room temperature for 15 min in 100 uL of 10 mM of NaOH.…”
Section: Study Population and Dna Samplesmentioning
confidence: 99%
“…Our real-time mCOP-PCR system is specific for detecting SMN1 deletions and does not provide any information about SMN2 copy number. If required for prognostic purposes, SMN2 copy number should be determined during a subsequent confirmatory assay or a second-tier assay [29,30]. However, SMN2 copy number does not always correspond to disease severity, and factors other than SMN2 copy number are also related to the severity of SMA [31].…”
Section: Limitations Of Smn1-deletion Detection As An Sma Screening Smentioning
confidence: 99%
“…Many methods for SMN1-specific detection have been reported [23,[25][26][27][28][29][30] that can be broadly divided into two methodological groups, A and B. Methods in group A are based on the co-amplification of SMN1 and SMN2 with common primers, and the presence of SMN1 is determined by an SMN1-specific binding of a fluorescence-labeled oligonucleotide probe [23,[25][26][27][28][29]. Methods in group B are based on amplification with SMN1-specific primers and the detection of the amplified SMN1 by a fluorescence-labeled oligonucleotide probe that commonly binds to SMN1/SMN2 [30].…”
Section: Inexpensive Method: No Requirement For Dna Extraction or Flumentioning
confidence: 99%